Contemporary trends in tactical formations and team success in Europe`s top-tier football leagues: a comparative analysis - Tokul, E.; Özçilingir, Ö. M.; Kaya, K.; Yilmaz, E. A.; Saray, D.; Agascioglu, E. A.; Demirli, A.; Erdem, K. (BMC Sports Science, Medicine and Rehabilitation, 2026)
This study examines the distribution of tactical formations and their relationship with team success across the six major European football leagues (Premier League, La Liga, Serie A, Bundesliga, Ligue 1, and TFF Super League) during the 2023-2024 season. A total of 2,132 matches and 4,038 formation data points were collected via OPTA Sportsdata and verified through fbref.com. The formations were grouped into eight main categories according to structural similarities. Statistical analyses included one-way analysis of variance (ANOVA) and chi-square tests. The findings indicate that the 4-2-3-1 system was the most frequently used formation, while the 3-4-3 provided the highest average points per match. The dominance of 4-2-3-1 was evident in the TFF Super League, whereas the 3-4-3 was more common in the Bundesliga and Serie A, and the 4-4-2 was more prevalent in La Liga. Conversely, five-defender formations yielded lower average points and limited success. In conclusion, the effectiveness of tactical formations is not solely determined by their structural advantages but also by their alignment with league culture, player profiles, and managerial strategies. These findings should be interpreted as a season-specific snapshot of formation usage patterns in the 2023-2024 season, rather than evidence of long-term tactical trends.